Remuneración de los docentes. - Rivera Berrazueta, Paul Oswaldo (2018)
The parents involvement in the student learning process is a task that involves strengthening the school-family bond. Hence, the present study has the purpose of determining the parental educational role as a means to improve the relationship of parents with the school. From the execution of a descriptive investigation and the application of a survey to the teachers in formation of the Basic Education Career of the Technical University of Cotopaxi. The results of the research show that the educational parental role can be described by the degree of participation of parents in educational tasks, family-school relationship benefits, decisions of the institution. In conclusion, there is little involvement of parents in the academic activities of their children, largely due to the existence of dysfunctional families, single parents, parents engaged in commercial activity, among others.